2018
DOI: 10.1016/j.jocd.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of Dual-Energy X-Ray Absorptiometry-Derived Body Composition Change in Athletes: A Review and Recommendations for Best Practice

Abstract: Dual-energy X-ray absorptiometry (DXA) is a medical imaging device which has become the method of choice for the measurement of body composition in athletes. The objectives of this review were to evaluate published longitudinal DXA body composition studies in athletic populations for interpretation of "meaningful" change, and to propose a best practice measurement protocol. An online search of PubMed and CINAHL via EBSCO Host and Web of Science enabled the identification of studies published until November 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 71 publications
2
53
0
Order By: Relevance
“…Nevertheless, it should be noted that the consecutive-day precision errors in the current study were within the acceptable limits for DXA precision as identified by the ISCD which are 3% for FM and 2% for LM [7]. Further, the precision error values were similar to those found in a number of studies as recently reviewed [8].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Nevertheless, it should be noted that the consecutive-day precision errors in the current study were within the acceptable limits for DXA precision as identified by the ISCD which are 3% for FM and 2% for LM [7]. Further, the precision error values were similar to those found in a number of studies as recently reviewed [8].…”
Section: Discussionsupporting
confidence: 87%
“…The ability to confidently quantify these small but potentially important changes in body composition can enable better refinement of interventions, and thus, potentially enhance athletic performance. The International Society for Clinical Densitometry (ISCD) recommends the application of the least significant change (LSC) in the interpretation of longitudinal body composition measurements, which is calculated using sameday repeat scans [7,8]. LSC quantifies precision based on two consecutive scans, thus identifying the technical error inbuilt into a specific piece of equipment for a given population [7].…”
Section: Conclusion: When Tracking Changes In Body Composition the Umentioning
confidence: 99%
“…The scale comprises 24 questions: 5 questions on pain evaluation, 2 questions on joint stiffness, and 17 questions on physical function [19]. The WOMAC scale has been widely used to evaluate hip and knee joint dysfunction and is a standard questionnaire for evaluating pain, joint stiffness, and dysfunction amongst patients with osteoarthritis [20]. A high score on the WOMAC index indicates severe OA.…”
Section: Experimental Process and Data Acquisitionmentioning
confidence: 99%
“…This method is widely used on account of its low cost, simple operation, and reliable results. A recent systematic review showed that DXA could be regarded as a new gold standard for measuring the body composition because it is highly correlated with nuclear magnetic resonance and computed X-ray tomography [20]. Up until now, DXA has been used to measure the bone mineral density and the body composition of athletes, thus providing a suitable reference for the training and diet plan [20].…”
Section: Introductionmentioning
confidence: 99%
“…The current imaging gold standard, magnetic resonance imaging (MRI), allows for objective, and accurate measures of muscle mass, but is expensive and its availability is limited, while alternative techniques, such as bioelectrical impedance analysis and air displacement plethysmography, lack precision . Dual x‐ray absorptiometry (DXA) has become increasingly prolific within elite and professional sport environments, and the reliability of the method in athletic populations has improved, but DXA does not measure muscle mass per se, but rather lean tissue mass.…”
Section: Introductionmentioning
confidence: 99%